2007
DOI: 10.1016/j.jvs.2006.08.068
|View full text |Cite
|
Sign up to set email alerts
|

The management of renal artery atherosclerosis for renal salvage: Does stenting help?

Abstract: Renal artery stenoses causing renal dysfunction can be safely treated via endovascular means. Rapidly decreasing renal function is associated with the response to renal artery angioplasty/stenting and helps identify patients for renal salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
(22 reference statements)
2
33
0
3
Order By: Relevance
“…All cases of atherosclerotic renal artery stenosis were managed successfully by stenting and kidney transplant. This is consistent with the safety of stenting and its capacity to restore renal function [28]. …”
Section: Discussionsupporting
confidence: 84%
“…All cases of atherosclerotic renal artery stenosis were managed successfully by stenting and kidney transplant. This is consistent with the safety of stenting and its capacity to restore renal function [28]. …”
Section: Discussionsupporting
confidence: 84%
“…Some studies have shown that revascularization is efficacious in improving hypertension control in 50–85% of patients [18], but these experiences are not replicated in the literature, and results in terms of renal functional outcome have been even more variable. Most of these studies have been retrospective [19], observational or non-randomised, and results have been conflicting [20,21]. Review of the many retrospective and prospective case series reported in the literature indicates that approximately 25% of patients show renal functional improvement, 25% deteriorate and 50% remain unchanged [12,22] following revascularization.…”
Section: Renal Revascularization In Arvdmentioning
confidence: 99%
“…Five-year patency following aortorenal bypass is 95.0%, compared to 55.6% for renal artery stenting. 7,10,[18][19][20] The five-year patency was assumed to be similar between patients who had no complications and those who experienced one or more complications. A primary patency of 75% was identified in the literature and used for aortorenal bypass patients who developed complications to determine whether this significantly influenced cost or value for aortorenal bypass compared to renal artery stenting, but none was found (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Patients have a 63% three-year dialysis-free survival, however up to 25% of patients experience a decline in renal function with negligible long-term improvement in hypertension. [5][6][7][8][9] Open surgical options include aortorenal bypass, iliorenal bypass, hepatorenal bypass, and splenorenal bypass. Other options include endarterectomy with patch angioplasty, and reimplantation of the renal artery.…”
Section: Introductionmentioning
confidence: 99%